2001
DOI: 10.1073/pnas.241411198
|View full text |Cite
|
Sign up to set email alerts
|

Directed polar secretion of protease from single cells of Vibrio cholerae via the type II secretion pathway

Abstract: Bacteria have long been thought of as little more than sacks of homogeneously distributed enzymes. However, recent cytological studies indicate that bacteria are compartmentalized with proteins involved in processes such as cell division, motility, chemotaxis, and development located at distinct sites. We have used the green fluorescent protein as a reporter to determine the cellular distribution of the extracellular protein secretion (eps)-encoded type II secretion complex responsible for extracellular secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(90 citation statements)
references
References 48 publications
4
84
2
Order By: Relevance
“…Previous studies with the Vibrio cholerae PulG homolog EpsG indicated that it clusters at the cell pole, consistent with the facts that type II secretion occurs at the pole in this bacterium and that other secreton components also accumulate there (53). In contrast, GFP-PrePulG and PulG-mRFP were evenly distributed throughout the E. coli inner membrane, consistent with previous data showing similar patterns of GFP-PulM and GFP-PulL distribution (10).…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies with the Vibrio cholerae PulG homolog EpsG indicated that it clusters at the cell pole, consistent with the facts that type II secretion occurs at the pole in this bacterium and that other secreton components also accumulate there (53). In contrast, GFP-PrePulG and PulG-mRFP were evenly distributed throughout the E. coli inner membrane, consistent with previous data showing similar patterns of GFP-PulM and GFP-PulL distribution (10).…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, a recent study on the type II secretion system of V. cholerae also showed discrete fluorescent foci along the cell periphery for different components of this macromolecular complex (37). This finding is in contrast to the polar localization pattern described earlier (22), which most likely resulted from an overexpression artifact (37). Indeed, Lybarger et al concluded that "chromosomal, intraoperon expression conditions are optimal for determining the intracellular locations of fusion proteins" (ref.…”
Section: Discussionmentioning
confidence: 88%
“…we could show that the pilus was able to localize to either of the two poles (e.g., the old or the new pole) (22) (Fig. S3).…”
Section: Construction Of Competence-gene Mutants and Assessment Of Theirmentioning
confidence: 98%
“…This observation leads to a particularly attractive model for the role of the PilA-containing ChiRP in the V. cholerae chitin utilization program that could explain why type IV pilus assembly complex genes reside in the same regulon with genes that encode chitin catabolic functions. This model incorporates the fact that the eps type II chitinase secretion apparatus and most type IV pilus assembly complexes localize to the cell pole (24). In view of these topographical features, the model predicts that the assembly complex for the ChiRP localizes to the same pole as the the eps type II secretion apparatus.…”
Section: Discussionmentioning
confidence: 99%